Kolaborasi Pentahelix Dalam Membangun Desa Wisata Berbasis Masyarakat - Antoni Hidayatullah; Muhamad Ali; Pahrudin Pahrudin (Universitas Hamzanwadi, 2023)
A tourist village is a form of integration between attractions, accommodation and supporting facilities presented in a structure of community life that is integrated with prevailing procedures and traditions. In developing a tourism village, the Petahelix collaboration is needed which is a very important collaboration because it can provide advantages and benefits to the community and the environment. With good integration, quality activities, facilities, services, and tourism experiences and benefits can be created. This study aims to find out how the pentahelix concept collaborates in building community-based tourism villages. This type of research includes qualitative research with data obtained directly through observation and interviews in Tourism Villages (Pringgasela Selatan and Labuhan Haji). The interviews in this study were conducted by determining informants consisting of five Pentahelix actors including government, academics, business/private businesses, mass media and the community who played a role in the development of Pringgasela Selatan Tourism Village and Labuhan Haji. The research results obtained indicate that it is necessary to increase the coordination and collaboration of pentahelix actors to be implemented in the Pringgasela Selatan and Labuhan Haji Tourism villages. Good coordination between pentahelix actors can help improve infrastructure, improve the quality of tourism products and develop more effective programs. With good collaboration, the community and the surrounding environment can experience significant benefits from sustainable tourism and have a positive impact on the local economy.